Biomechanical analysis of the start in ski cross and snowboard cross - Olvermann, M.; Frühschütz, H.; Goll, M.; Spitzenpfeil, P.; Huber, A. (ISBS Proceedings Archive (Michigan), 2017)
Ski Cross and Snowboard Cross are developing disciplines in winter sports and part of the Olympic Games since 2010. Argüelles et al. (2011) reported that the starting phase seems to be a very important part of the entire race. The purpose of this study was to analyse the kinetics and kinematics of different starting movements in ski cross and snowboard cross and to identify the relevant parameters for an effective start. The national teams of the German ski and snowboard federation were examined with totally 21 athletes. The test was proceeded in a ski hall on artificial snow with a world-cup approved start gate. As expected, the start is more effective, if the athlete generates a higher force value during the pull phase. A good force transmission depends on body position and acceleration distance. These results are suitable for recommendation for coaches and athletes.